Experimental Study on Deformation and Damage Evolution of Cracked Red Sandstone Under Freeze–Thaw Cycles - Xize Han; Guangchen Sun; Helin Fu; Chao Tan; Zailong Huang; Peng Yin; Qishu Zhang; Wenchen Fan; Shuiping Yin (Applied Sciences)
Cracked rock masses in cold regions are subjected to freeze–thaw cycles over extended periods, resulting in freeze–thaw deformation. The combined effects of freeze–thaw cycling and the depth of cracks significantly influence the stability and durability of underground rock engineering in these regions. In some cold regions with minimal annual rainfall, rock masses are unable to absorb external water during freeze–thaw cycles. As freeze–thaw deformation progresses, the rock transitions naturally from a saturated state to an unsaturated state. To investigate the deformation damage mechanisms and evolution patterns of saturated red sandstone with initial non-penetrating cracks of varying depths (20 mm, 30 mm, 40 mm) under freeze–thaw cycling conditions without external water replenishment and with naturally varying saturation levels, relevant freeze–thaw cycle experiments and strain monitoring were conducted. The results indicate that cracked red sandstone experiences residual strain in each freeze–thaw cycle, which gradually accumulates, leading to irreversible freeze–thaw damage deformation. The cumulative residual strain of the rock specimen after 45 freeze–thaw cycles was 40.69 times greater than the residual strain from the first cycle. Additionally, the freeze–thaw strain characteristic values exhibited a clear correlation with crack depth. These findings provide experimental methods and data references for analyzing the deformation and failure mechanisms of cracked rock induced by freeze–thaw damage in cold regions.